Pelvic organ cross-sensitization to enhance bladder and urethral pain behaviors in rats with experimental colitis. (22nd January 2015) - Yoshikawa, S.; Kawamorita, N.; Oguchi, T.; Funahashi, Y.; Tyagi, P.; Chancellor, M.B.; Yoshimura, N.
Highlights: TNBS-induced colitis significantly enhances licking and freezing behaviors in rats. DRG neurons innervating both colon and lower urinary tract are shown. TRPV1 mRNA is increased in the bladder, urethra and S1 DRG in colitis rats. MPO activity is increased in colon, but not in bladder or urethra, after colitis. Abstract: Neural cross-sensitization has been postulated as a mechanism underlying overlaps of chronic pelvic pain disorders such as bladder pain syndrome/interstitial cystitis (BPS/IC) and irritable bowel syndrome (IBS). Animals with experimental colitis have been used to study the underlying mechanisms for overlapped pelvic pain symptoms, and shown to exhibit bladder overactivity evidenced by frequent voiding; however, it has not directly been evaluated whether pain sensation derived from the lower urinary tract is enhanced in colitis models. Also, the cross-sensitization between the colon and urethra has not been studied previously. In the present study, we therefore investigated pain behaviors induced by nociceptive stimuli in the lower urinary tract and the involvement of C-fiber afferent pathways using rats with colitis induced by intracolonic application of 2, 4, 6-trinitrobenzenesulfonic acid (TNBS). In TNBS-induced colitis rats at 10 days, intravesical application of resiniferatoxin (RTx) induced a significantly greater number of episodes of both licking and freezing behaviors, which were reduced by capsaicin-sensitive C-fiber afferent desensitization. Histochemical studies using fluorescent dye tracers injected into the colon, bladder or urethra showed that dichotomized afferent neurons comprised 6.9–14.5% of L1, L6 and S1 dorsal root ganglion (DRG) neurons innervating the colon or the lower urinary tract. Transient receptor potential vanilloid 1 (TRPV1) mRNA expression was significantly increased in, the bladder, urethra and S1 DRG in colitis rats. An increase in myeloperoxidase (MPO) activity was found in the colon, but not in the bladder or urethra after intracolonic TNBS treatment. These results indicate that TNBS-induced colitis increased pain sensitivity in the bladder and urethra via activation of C-fiber afferent pathways due to colon-to-bladder and colon-to-urethral cross-sensitization, suggesting the contribution of pelvic organ cross-sensitization mechanisms to overlapped pain symptoms in BPS/IC and IBS.